QAULAN SADIDAN PRINCIPLES AND FACTUALITY IN PUBLIC BROADCASTING INSTITUTION NEWS - Rachmat Kriyantono (Faculty of Social Sciences and Humanities Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2019)
Abstract. This study aims to test the hypothesis that, as a public broadcasting institution that serves the public interest, non-commercial, and the majority of audiences are Muslim, the principle of qaulan sadidan has been widely adopted in TVRI news. Islam has provided a grand-theory for the study of communication and journalistic, namely qaulan sadidan. This principle was later recognized in the Western academic world as factuality, which is part of the news objectivity. By using the content analysis method on 146 news items from September 23, 2018 to March 29, 2019, this study found that the principle of qaulan sadidan has dominated the TVRI news although there are still news that do not yet contain elements of factuality. Many TVRI news articles are written containing 5W and 1H. This study also used interviews with senior journalist to confirm the data from the content analysis. The interviews found that management had not periodically socialized the relevance of Islamic values to journalistic practices, the element of the